Perilaku Merokok dan Jenis Kelamin Laki-Laki sebagai Determinan Kejadian Hipertensi pada Tenaga Kerja di PTPN IX Ngobo, Karangjati, Kabupaten Semarang - Afiatna, Puji; Purbowati, Purbowati (Program Studi Gizi Jurusan Ilmu Kesehatan Masyarakat Fakultas Ilmu Keolahragaan Universitas Negeri Semarang (UNNES) bekerjasama dengan Persatuan Ahli Gizi (PERSAGI), 2020)
Background : Healthy physical condition will support the optimal productivity. Hypertension is a non-communicable disease which is one of the problems in public health in Indonesia. Hypertension can cause an increase in morbidity and mortality rates, as well as decrease the economy and work productivity. Objective : To identify determinants of the hypertension in the workforce at PTPN IX Ngobo, Karangjati, Semarang Regency. Methods : This research is an analytical research with cross-sectional approach. There were 75 people as samples with age range of 18-57 years old taken by consecutive sampling method. Blood pressure was measured using a digital tensimeter. Nutritional status was determined based on Body Mass Index (BMI). Body fat percentage and visceral fat were measured with Bio Impedance Analysis (BIA) tool. Data on intake adequacy were collected by conducting interviews using the Semi Quantitative Food Frequency Questionnaire (SQFFQ). Other variables were work load, work shift, number of family members who were dependent, economic status and smoking behavior. Data analysis was performed using multivariate logistic regression test. Results : 70.7% of the subjects were male. 60% of subjects had hypertension. The mean age of the subjects was 41.44 years, most of which fall into the category of late adulthood (64%). There are two factors that mostly influence the hypertension, which are gender (male) and smoking behavior that can be used to predict the hypertension. The probability of a worker who smokes and is male to suffer hypertension is 68.5%.